All for love three historical romance novellas of love and laughter (Bethany House, a division of Baker Publishing Group, 2017)
"Three of Christian historical fiction's beloved authors come together in this romantic and humorous collection of novellas featuring prequels to their latest series. New and loyal fans alike will enjoy these novellas previously released only as ebooks. Connealy's "The Boden Birthright" journeys to the Old West, where ranch hand Chance Boden's determination to be his own boss is challenged by his employer's pretty daughter. Hunter's "A Lady of Esteem" follows a Regency-era young lady whose chance at love and reputation in society are threatened by a nasty rumor. Turano's "At Your Request" tells of a young woman who is humbled at her newly lowered status in society when she is reunited with the very man whose proposal she rejected."--Amazon.